Inhibitory Effect of Piracetam on Platelet-rich Thrombus Formation in an Animal Model - Stockmans, F.; Deberdt, W.; Nyström, Å.; Nyström, E.; Stassen, J. M.; Vermylen, J.; Deckmyn, H. (Thrombosis and Haemostasis, 1998)
Intravenous administration of piracetam to hamsters reduced the formation of a platelet-rich venous thrombus induced by a standardised crush injury, in a dose-dependent fashion with an IC50 of 68 ± 8 mg/kg. 200 mg/kg piracetam also significantly reduced in vivo thrombus formation in rats. However, in vitro aggregation of rat platelets was only inhibited with piracetam-concentrations at least 10-fold higher than plasma concentrations (6.2 ± 1.1 mM) obtained in the treated animals. No effects were seen on clotting tests.In vitro human platelet aggregation, induced by a variety of agonists, was inhibited by piracetam, with IC50’s of 25-60 mM. The broad inhibition spectrum could be explained by the capacity of piracetam to prevent fibrinogen binding to activated human platelets. Ex vivo aggregations and bleeding times were only minimally affected after administration of 400 mg/kg piracetam i.v. to healthy male volunteers, resulting in peak plasma levels of 5.8 ± 0.3 mM.A possible antiplatelet effect of piracetam could be due to the documented beneficial effect on red blood cell deformability leading to a putative reduction of ADP release by damaged erythrocytes. However similarly high concentrations were needed to prevent stirring-induced “spontaneous” platelet aggregation in human whole blood.It is concluded that the observed antithrombotic action of piracetam cannot satisfactorily be explained by an isolated direct effect on platelets. An additional influence of piracetam on the rheology of the circulating blood and/or on the vessel wall itself must therefore be taken into consideration.